2020
DOI: 10.1177/0049124120914924
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Error in Data Collection Combining Mobile Surveys With Passive Measurement Using Apps: Data From a German National Survey

Abstract: Researchers are combining self-reports from mobile surveys with passive data collection using sensors and apps on smartphones increasingly more often. While smartphones are commonly used in some groups of individuals, smartphone penetration is significantly lower in other groups. In addition, different operating systems (OSs) limit how mobile data can be collected passively. These limitations cause concern about coverage error in studies targeting the general population. Based on data from the Panel Study Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 28 publications
4
49
0
1
Order By: Relevance
“…Table A1 in the Appendix displays the selection process of participants from participants of the PASS study to our analysis sample. Coverage and nonresponse analyses are beyond the scope of this article but are reported in the studies of Keusch et al (2020aKeusch et al ( , 2020b. Table 1 shows that even for the times when a measurement was collected, in several cases, geolocation failed (4) leading to missing geocoordinates.…”
Section: The Iab-smart Studymentioning
confidence: 99%
“…Table A1 in the Appendix displays the selection process of participants from participants of the PASS study to our analysis sample. Coverage and nonresponse analyses are beyond the scope of this article but are reported in the studies of Keusch et al (2020aKeusch et al ( , 2020b. Table 1 shows that even for the times when a measurement was collected, in several cases, geolocation failed (4) leading to missing geocoordinates.…”
Section: The Iab-smart Studymentioning
confidence: 99%
“…Moreover, mobile phone applications are able to provide respondents with information and questionnaires. Although previous research has shown that consent to using mobile phone apps is selective, there is little evidence on the reasoning behind this selectivity (an exception is the recent publication by Keusch & Bähr et al, 2020). Previous research on face-to-face interviews and interviewer effects gives rise to the hypothesis that interviewers play a crucial role.…”
Section: Interviewer Effects In Survey Datamentioning
confidence: 99%
“…Despite its great potential, evidence regarding the utility of smartphones and apps in social science research is mixed and many challenges remain. To begin with, presumably not all members of a target population own a smartphone (Keusch, Bähr et al, 2020). Therefore, field institutes need to find solutions that avoid underrepresenting substantial parts of the target population such as the elderly or poor (Fuchs & Busse, 2009; Hoogeveen et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The growing rate of smartphone adoption does not solve the coverage problem if those who use smartphones are different from those who do not in the characteristics of interest and if individuals do not have the smartphone skills required to install apps or share smartphone sensor data in browser. For example, in Germany, smartphone ownership correlates with age, educational attainment, immigrant status, nationality, region, and community size (Keusch, Bähr, et al, 2020). These variables are related to many concepts of interest in the social sciences.…”
Section: Challenges Of Sensor and App-based Data Collectionmentioning
confidence: 99%
“…These variables are related to many concepts of interest in the social sciences. Moreover, among those who use smartphones, there is an operating system divide: iOS users (i.e., iPhone owners) differ significantly from smartphone owners whose phones run on the Android OS in attitudinal and behavioral characteristics; and these differences cannot be corrected by weighting based on sociodemographic information (Keusch, Bähr, et al, 2020). Researchers implementing their studies with sensors on smartphones should be cognizant of possible existence of such biases.…”
Section: Challenges Of Sensor and App-based Data Collectionmentioning
confidence: 99%